Utilisation of the National Antiretroviral Therapy Guidelines among health care professionals working in Abuja treatment centres, Nigeria - Lindiwe I. Zungu; Ugbede O. Abu; Gboyega A. Ogunbanjo; Geoffrey K. Setswe (AOSIS, 2009)
Background: Access to and utilisations of the National Antiretroviral Treatment Guidelines (NATG) are valuable factors for effective programme implementation. The objective of this study was to investigate the accessibility of the NATG and their utilisation by health care professionals from five treatment centres in Abuja, Nigeria. Method: A quantitative cross-sectional descriptive survey was conducted in 2007 using purposively sampled health care professionals. Questionnaires were self-administered to participants who consented in writing to participate in the survey. Results: 97 health care professionals participated in this study with about equal numbers of men and women: 48 (49.5%) women and 49 (50.5%) men. Of these, 21.6% were unaware of the existence of the NATG in their treatment centres. More than half (51.5%) reported that they did not have access to the NATG as opposed to those (48.5%) who had access to the guidelines. Furthermore, 16.5% of the participants confirmed that they had access to an institutional copy of the NATG while 14.4% indicated that they had individual copies and only 3.1% stated that they had individual copies and access to the hospital copy as well. Regarding utilisation of the NATG, 41.2% rarely used them, 32.9% never used them and only 25.7% often used them. The most frequent use of the NATG was among pharmacists (38.1%) compared to the least frequent use among nurses (20.0%). Conclusion: Poor accessibility of the NATG may have a negative impact on guidelines utilisation among health care professionals in Nigeria.